2022
DOI: 10.1038/s41598-022-11287-5
|View full text |Cite
|
Sign up to set email alerts
|

Whole genome sequencing of multidrug-resistant Mycobacterium tuberculosis isolates collected in the Czech Republic, 2005–2020

Abstract: The emergence and spread of resistant tuberculosis (TB) pose a threat to public health, so it is necessary to diagnose the drug-resistant forms in a clinically short time frame and closely monitor their transmission. In this study, we carried out a first whole genome sequencing (WGS)-based analysis of multidrug resistant (MDR) M. tuberculosis strains to explore the phylogenetic lineages diversity, drug resistance mechanisms, and ongoing transmission chains within the country. In total, 65 isolates phenotypical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 55 publications
2
7
0
Order By: Relevance
“…DNA extraction and WGS were performed according to the procedure published in our previous study [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…DNA extraction and WGS were performed according to the procedure published in our previous study [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…The clustering rate (15.8%) of drug-resistant MTB isolates in this low-incidence setting was lower than that (48.5%) in Thailand, which is a high-incidence setting 22 . Previous studies reported a high clustering rate of MDR isolates in the Czech Republic (29.23%), Spain (48.4%), and EU countries (51.6%) 17,23,24 . The lower clustering rate of drug-resistant MTB in Finland may be due to smaller immigrant populations from high-incidence countries in Finland than that in other EU countries.…”
Section: Discussionmentioning
confidence: 92%
“…The WHO recently recommended that, when individuals are being evaluated for extrapulmonary TB using cerebrospinal fluid, lymph nodes, and tissue specimens, MTBC detected trace result be considered as bacteriological confirmation of TB (i.e., a true positive result), and these patients should be treated with an appropriate regimen using first-line TB drugs unless the patients are at high risk of having MDR-TB [5]. Direct whole-genome sequencing (DWGS) of M tuberculosis enables the prediction of drug resistance either from bacterial strains or directly from smearpositive sputum samples [13,14]. DWGS has also been applied to smear-negative sputum samples with some success [14].…”
Section: Discussionmentioning
confidence: 99%